5PSQ-038 Safety and effectiveness of HIV post-exposure prophylaxis. (March 2019) - Fernandes, A; Brito, A; Lourenço, L; Domingos, S; Alcobia, A
Abstract : Background: HIV post-exposure prophylaxis (PEP) aims at preventing HIV transmission through the intake of antiretroviral treatment (ART), after an occupational (OC) or non-occupational context (NOC) exposure. Purpose: In order to determine the safety and effectiveness of HIV PEP this study aimed to characterise patients who initiated PEP. Material and methods: Retrospective descriptive study, between January 2016 and September 2018. All the patients above 18 years' old who presented risk of HIV contact and were medicated with PEP in the hospital pharmacy (HP), were included. Data were obtained from electronic medical records. Results: A total of 105 PEP were dispensed in HP, 52.4% in an OC and 47.6% in a NOC, mostly female (64.8%) with a mean age of 35.5±12.9 years. In OC, females prevailed (83.6%). PEP intake was justified when there was contact with infected fluids through: accidental puncture (83.6%), eyeball contamination (12.7%) and skin-mucus membranes lacerations (3.6%). 41.5% were healthcare work-related accidents. Regarding NOC, 56.0% were male. Prescriptions reasons were: unprotected sex 34.7%, condom rupture 32.7%, rape 22.5% and others 10.2%. Source HIV serology was unknown in 70.5% of the cases. From the 105 PEP treatment initiated, six were suspended after knowing the source of HIV negative serology. The initial ART mostly used was raltegravir (RAL) +emtricitabine/tenofovir (3TC/TDF) (78%). Others ART were initially used (22%), provided either by the emergency service or by another HP. RAL +3 TC/TDF combination was the main choice due to its tolerability profile and recent guidelines. 1 Twenty-six patients experienced adverse reactions (AR) such as gastrointestinal discomfort, dizziness and heart palpitations. 63.8% patients completed 6 months post-exposure serological follow-up, with no cases of seroconversion, and were discharged. 18.1% of patients missed the follow-up serology and appointments, and the remaining patients are still are under evaluation. Prophylaxis was proposed to five patients, four of them for systematic risk behaviours and one for serodiscordant partner. Conclusion: PEP has proved to be effective and safe (low severity AR) preventing HIV transmission. Variation of ARV used in PEP reflects the updating of the guidelines. 1 References and/or acknowledgements: 1. Updated Guidelines for Antiretroviral Postexposure Prophylaxis After Sexual, Injection Drug Use, or Other Nonoccupational Exposure to HIV. United States, 2016, CDC. No conflict of interest.